Coal-fired power stations - Kruitwagen, L; Collins, S; Caldecott, B (Royal Society of Chemistry, 2017)
Thermal coal-fired power stations currently provide approximately 40% of the world's electricity and 30% of the world's generating capacity. Approximately 83% of all coal demand is thermal coal, and 61% of primary coal energy is consumed in power stations. Notwithstanding alternatives in coal gasification, coal-to-liquids, and chemical looping technologies, the future of coal in the 21st century depends largely on the future of coal combustion for power generation. This chapter provides a technical overview of coal-fired power stations and their exposure to a wide array of environment-related risks, including greenhouse gas emissions and stranded assets; water consumption and competition with agriculture, industry, and domestic uses; climate stresses induced by anthropogenic climate change (of which they are the primary cause); competition with renewables and generating flexibility; costs and trade-offs of mitigation options; retrofitability with carbon capture and storage; and the availability of finance. The future of coal in the 21st century depends largely on the response of policy makers, industry and the concerned public to these risks.